Bacteriological Contamination of Cell Phones of Health Students at a University Center in Recife - PE (Research, Society and Development, 2021)
With the ease of using a cell phone, the phone is taken to many different places, some of which contain pathogenic microorganisms, such as bathrooms, hospitals, and laboratories. Cell phones can be contaminated by infectious bacteria and fungi. Thus, the present study aimed to identify the microorganisms present in cell phones of health students from a University Center in Recife - PE. This is a quantitative cross-sectional study carried out in March 2020. Thirty samples were collected from cell phones of students from the Biomedicine course.  However, 15% of the students did not wash their hands before meals, 81% ate with the cell phone beside them, and only 4% washed their hands and ate without the proximity of the device. The most common cause of contamination of mobile devices is the lack of sanitation of the cell phones and hands. As a result of the tests, 100% of the cell phones collected had microbiological growth, 52% being gram-positive and 48% gram-negative. For the gram-positive bacteria, Catalase tests were performed, of which 48% were positive stating that they were Staphylococcus sp and 4% negative stating that they were Streptococcus sp. In the positive Catalase results, Coagulase tests were performed with 30% of the positive results, assuming the presence of Staphylococcus aureus. These bacteria can be pathogens, that is, they alter the functioning of the body causing illness. According to the results obtained, all the devices tested presented bacterial contamination by Streptococcus spp. and Staphylococcus spp. There was also the presence of bacteria from the Enterobacteriaceae family, such as Salmonella sp. and Klebsiella sp.